2015
DOI: 10.1016/j.celrep.2015.08.029
|View full text |Cite|
|
Sign up to set email alerts
|

Testing the Effect of Internal Genes Derived from a Wild-Bird-Origin H9N2 Influenza A Virus on the Pathogenicity of an A/H7N9 Virus

Abstract: Since 2013, avian influenza A(H7N9) viruses have diversified into multiple lineages by dynamically reassorting with other viruses, especially H9N2, in Chinese poultry. Despite concerns about the pandemic threat posed by H7N9 viruses, little is known about the biological properties of H7N9 viruses that may recruit internal genes from genetically distinct H9N2 viruses circulating among wild birds. Here, we generated 63 H7N9 reassortants derived from an avian H7N9 and a wild-bird-origin H9N2 virus. Compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Recent cases (2013) of avian-to-human transmission of avian influenza A virus subtypes included H7N9, H6N1, and H10N8 6, 7, 8. The case-fatality rate in over 600 cases of H7N9 infections was ∼30% 1, 9. Most recently, the World Health Organization reported another 120 cases since September 2016 resulting in 37 deaths 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent cases (2013) of avian-to-human transmission of avian influenza A virus subtypes included H7N9, H6N1, and H10N8 6, 7, 8. The case-fatality rate in over 600 cases of H7N9 infections was ∼30% 1, 9. Most recently, the World Health Organization reported another 120 cases since September 2016 resulting in 37 deaths 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Of the H9N2-like PB1s, 18 isolates contained a full length PB1-F2 (90aa), 5 had a minor truncation (76aa), and a single isolate had a major truncation (27aa). 76aa long PB1-F2s from H9N2 viruses has previously been implied to increase the virulence of H7N9 viruses in mice but are thought not to interfere with function ( Gibbs et al, 2003 , Su et al, 2015 ). PB1-F2 functional knockouts, similar to the 27aa variant seen, have also been shown to increase virulence of avian influenza viruses ( Gibbs et al, 2003 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, we showed that diverse wild bird H9N9 influenza virus genes elevated the virulence of a H7N9 virus (Su et al, 2015). Recently, cases of human infections with newly reasserted influenza A (H7N9) virus have been continuously reported in China (Sha et al, 2016; Shen and Lu, 2017).…”
Section: Discussionmentioning
confidence: 99%